The econometric model of evaluation and selection of priority strategies of reducing risks of the total loan portfolio of commercial banks - M. A. Gorskij; E. A. Zakrevskaya (Путеводитель предпринимателя)
The article observe the problem in using the econometric approach to the assessment of the total loan risk appearing in portfolio of assorted risk of commercial bank loans. It is proposed to use the linear regression model of dependence between the value of the bank’s own funds (as the most ris-sensitive portfolio characteristic) and the current values of particular indicators of risk K1-K7 (the quantities of reserves and own funds on the previous period of time) in assessing the risk. Different versions of linear regression models are calculated according to the specific loan portfolio of the bank, which allow to asses credit risk for different scenarios of implementation of credit strategies.